Pushing up or pushing out - an initial investigation into horizontal- versus vertical-force training on swimming start performance: a pilot study - Thng, S.; Pearson, S.; Keogh, J. W. L. (PeerJ, 2021)
Background: The block phase in the swimming start requires a quick reaction to the starting signal and a large take-off velocity that is primarily horizontal in direction. Due to the principle of specificity of training, there is a potential benefit of performing a greater proportion of horizontal force production exercises in a swimmers` dry-land resistance training sessions. Therefore, the purpose of this pilot study was to provide an insight into the effects of a horizontal- (HF) vs vertical-force (VF) training intervention on swim start performance. Methods: Eleven competitive swimmers (six males (age 20.9 ± 1.8 years, body mass 77.3 ± 9.7 kg, height 1.78 ± 0.05 m) and five females (age 21.4 ± 2.0 years, body mass 67.5 ± 7.4 kg, height 1.69 ± 0.05 m)) completed 2 weekly sessions of either a horizontal- or vertical-force focused resistance training programme for 8 weeks. Squat jump force-time characteristics and swim start kinetic and kinematic parameters were collected pre- and post-intervention. Results: Across the study duration, the swimmers completed an average of nine swimming sessions per week with an average weekly swim volume of 45.5 ± 17.7 km (HF group) and 53 ± 20.0 km (VF group), but little practice of the swim start per week (n = 9). Within-group analyses indicated a significant increase in predicted one repetition maximum (1RM) hip thrust strength in the HF group, as well as significant increases in grab resultant peak force but reductions in resultant peak force of the block phase for the VF group. No significant between-group differences in predicted 1RM hip thrust and back squat strength, squat jump force-time and swim start performance measures were observed after 8 weeks of training. Significant correlations in the change scores of five block kinetic variables to time to 5 m were observed, whereby increased block kinetic outputs were associated with a reduced time to 5 m. This may be indicative of individual responses to the different training programmes. Discussion: The results of this current study have been unable to determine whether a horizontal- or vertical-force training programme enhances swim start performance.